WAR AND THE LABOR MARKET IN UKRAINE - Olha Cheromukhina (Izdevnieciba "Baltija Publishing", 2022)
The purpose of the paper is to study the transformation process of the labor market of Ukraine during the war period; the impact of external and internal migration on the labor market; to provide recommendations for the stabilization of the labor market in the post-war period. Methodology. Research methods such as classification and analysis were used in the work on various aspects of the labor market during the war. The article provides a comparative analysis of the state of the labor market in the war and post-war periods, a noticeable vacancy in the labor market. The relocation of a significant part of the business to the western regions was also taken into account, which in turn resulted in a significant social and employment burden in these regions. It was concluded that despite the difficult conditions, the labor market has shown its ability to adapt to the new conditions. Practical implications. The impact of the war on various sectors of the economy has had devastating consequences, but as time has shown, the labor market has the ability to recover and adapt to new conditions. Thus, the example of the labor market in the Carpathian region shows that the risks and positive shifts in the social burden due to a large flow of internally displaced persons are taken into account. Value/originality. The article offers practical recommendations for the restoration of the labor market after the end of the war. Stabilization of the labor market should become one of the most important tasks of state policy, where it will be necessary to take into account the emergence of various population groups (people with disabilities) who suffered from military aggression, since Ukraine is experiencing significant human losses, which are reflected in the labor market.